Pengembangan Bioaktivator Berbasis Mikroba Berbagai Jenis Mol Untuk Pengomposan Limbah Tandan Kosong Kelapa Sawit Dalam Memperbaiki Sifat Tanah Bekas Tambang Batubara - Muhamad Hidayanto; Nurul Puspita Palupi; Roro Kesumaningwati; Zainudin Zainudin (Universitas Widya Gama Mahakam, 2017)
Improvement of agricultural development requires improvement of supporting factors of agricultural cultivation, especially the improvement of soil conditions using organic fertilizers. Organic fertilizers should go through the composting process to provide nutrients faster for plants. The composting process requires bioactivators to accelerate the decomposition of organic matter. Selection of bioactivators used in the composting process should be more careful considering each organic material has a different C / N ratio. Composting of organic materials with low C / N ratios generally does not have many obstacles, but the composting of organic materials with high C / N as in oil palm empty bunches requires a bioactivator capable of decomposing high levels of lignin in oil palm empty bunches. Development of bioactivators is a step that must be done in order to find a bioactivator that can accelerate the decomposition process, especially for organic materials with high C / N as in oil palm empty bunches. The research stages include: Identification, isolation and selection of potential microbials from maschy mole mol, gamal leaf mole, and fish waste mole, Analysis of mole chemistry, Mole application test to waste of empty palm oil bunches. The experimental method used in the fermentation stage of waste bunch of empty palm oil with 2 factors. The first factor is the MOL type, the second factor is the MOL concentration. The first factor consists of 3 treatments, the second factor consists of 4 treatments so that there are 12 treatments. The experiment was performed with 4 replications. First Factor; p1 = mol snail mas (km), p2 = mol gamal leaf (dg), p3 = mol of fish waste (li). The second factor was k1 = 100 ml of bioactivator / liter water solution, k2 = 150 ml of bioactivator / liter water solution, k3 = 200 ml of bioactivator / liter water solution, k4 = 250 ml of bioactivator / liter water solution.The results showed 1) the microorganisms identified in Koong Mas mole were Black Niger Aspergillus, Penicillium, and Trichoderma. In MOL Leaves of Gamal are Bacillus Biru, Bacillus Merah, Pythium, and Trichoderma. In MOL Fish Waste is Thricoderma. 2) Compost of empty palm oil bunches has not been decomposed perfectly because it has C / N> 25, but has provided nutrient elements of pH, total N, and K total according to SNI 19-7030-2004 standard. The high C / N ratio is probably due to environmental factors ie high temperatures at the composting site and the lack of moisture in the compost thus inhibiting the decomposition process. Key words: Local microorganisms, organic farming, and bioactivators